2018
DOI: 10.1111/jcmm.13912
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin as a potential target in the reversibility of pulmonary arterial hypertension secondary to congenital heart disease

Abstract: BackgroundThe reversibility of pulmonary arterial hypertension (PAH) in congenital heart disease (CHD) is of great importance for the operability of CHD. Proteomics analysis found that transgelin was significantly up‐regulated in the lung tissue of CHD‐PAH patients, especially in the irreversible group. However, how exactly it participated in CHD‐PAH development is unknown.MethodsImmunohistochemical staining and Western blot were performed for further qualitative and quantitative analysis of transgelin in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Transgelin is a 22 kDa protein that is widely found in smooth muscle tissues ( 15 ). Transgelin is an actin gelatin that is sensitive to changes in transformation, mutation, and shape ( 16 ). However, few studies have investigated its function.…”
Section: Introductionmentioning
confidence: 99%
“…Transgelin is a 22 kDa protein that is widely found in smooth muscle tissues ( 15 ). Transgelin is an actin gelatin that is sensitive to changes in transformation, mutation, and shape ( 16 ). However, few studies have investigated its function.…”
Section: Introductionmentioning
confidence: 99%
“…Other promising proteins include profilin 1, which overexpression is sufficient to induce cardiomyocyte hypertrophy and sarcomere remodeling, and silencing attenuates the hypertrophic response 45 . Furthermore, 14-3-3 protein, having an anti-apoptotic role through phosphorylation-dependent binding 46 and transgelin-2, that is an actin‐binding protein implicated in actin dynamics which induce cell proliferation and migration 47 are worthy of our attention. Also, we have observed increased abundance of calreticulin, that is an effective inducer of cardiac growth, which activation might be involved in hypoxic signaling leading to pulmonary hypertension; calreticulin activity may be inhibited by cyclosporin A, thus preventing RV hypertrophy 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Transgelins are a family of proteins that were discovered decades ago ( Lees-Miller et al, 1987 ; Shapland et al, 1993 ). They are involved in many diseases, including asthma, hypertension, diabetes and cancer, but the role of transgelins in cancer is not very clear ( Huang et al, 2018 ; Sun et al, 2018 ; Varberg et al, 2018 ; Yin et al, 2018 ). Recently, studies have shown that transgelins are associated with CRC metastasis.…”
Section: Introductionmentioning
confidence: 99%